Cohort research analysis of disaster experience, preparedness, and competency-based training among nurses. - Krzysztof Goniewicz; Mariusz Goniewicz; Frederick M Burkle; Amir Khorram-Manesh (PLoS ONE, 2021)
Introduction It is expected that in unforeseen situations, nurses will provide appropriate medical interventions, using their expertise and skills to reduce the risks associated with the consequences of disasters. Consequently, it is crucial that they are properly prepared to respond to such difficult circumstances. This study aimed to identify the factors influencing the basic competences of nurses in disasters. Materials and methods The survey was directed to 468 nurses from all medical centres in Lublin. IBM SPSS Statistics version 23 was used for statistical analyses, frequency analysis, basic descriptive statistics and logistic regression analysis. The classical statistical significance level was adopted as α = 0.05. Results Based on the logistic regression analysis, it was found that work experience, workplace preparedness, as well as training and experience in disaster response are important predictors of preparedness. Conclusions These findings indicate that the nurses' core competencies for these incidents can be improved through education and training programmes which increase their preparedness for disasters. Nurses are among the most important groups of healthcare professionals facing a disaster and should be involved in all phases of disaster management, such as risk assessment and pre-disaster planning, response during crisis situations and risks' mitigation throughout the reconstruction period.